Analysis of Concentration and Balance On The Accuracy of Kicking The Ball In SSB Bank Sulselbar Players - Jaya, Sonyman; Saharullah, Saharullah; Arimbi, Arimbi; Hudain, Muh. Adnan; Juhanis, Juhanis (UNIVERSITAS NEGERI MAKASSAR, 2025)
This study aims to determine the contribution of concentration to the accuracy of kicking the ball in Bank Sulselbar players, to determine the contribution of balance to the accuracy of kicking the ball in Bank Sulselbar players, and to determine the contribution of concentration and balance to the accuracy of kicking the ball in Bank Sulselbar players. This study uses a quantitative research type with a regression approach. To determine the magnitude of the influence and significance between the variables of concentration and balance on the accuracy of kicking the ball using multiple linear regression tests. The sample taken for this study was 20 SSB Bank Sulselbar players. The data collection process with three different tests, namely the concentration level measurement test, the modified bass test of dynamic balance test, and the soccer shooting ability test. The data analysis techniques used are descriptive analysis, normality test and regression test using the SPSS program. Based on the results of data analysis, the results of hypothesis testing and the results of the discussion of the research that has been obtained, it can be explained that the conclusion in this study There is a significant contribution of 28.4 percent of concentration to the accuracy of kicking the ball in SSB Bank Sulselbar players. There is a significant contribution of 33.8 percent of the balance to the accuracy of kicking the ball in SSB Bank Sulselbar players. And there is a significant contribution of 59.2 percent of concentration and balance to the accuracy of kicking the ball for SSB Bank Sulselbar players.